"Who over 65 is online?" Older adults' dispositions toward information communication technology. (February 2015) - Vroman, Kerryellen G.; Arthanat, Sajay; Lysack, Catherine
Highlights: A distinctive dichotomous pattern of ICT use among older adults emerged. Older adults' main ICT activities involved family/social communication and accessing information. Age, education, attitudes, and socio-personal characteristics were associated with ICT use. Older adults 65–70 with higher education and/or living with a spouse were more likely to use ICT. Older adults, who adopt ICT, valued their ICT activities as important in their lives. Abstract: This study is part of a research project that examines patterns of information communication technology (ICT) use, social participation, and health of older adults (age 65+) residing in the New England region. Specifically, we surveyed the breadth of ICT use, technology experiences, and socio-personal characteristics of 198 older adults and analyzed the dispositional correlates of ICT adoption. Results showed that majority of participants used ICT to maintain family and social connections and to access information on health and routine activities. Those aged 65–70 with higher education and/or living with a spouse/partner were more likely to use ICT. Key relationships between ICT use and perspectives on technology were found. Higher ICT use was associated with self-perceived socio-personal characteristics such as being "satisfied with activities", "persevering", "physically and emotionally independent" and having a "positive outlook". Whereas, the majority of non-users reported that their activities did not change across time and that they felt "intimidated" and "anxious" with technology. The performance of ICT-based activities and/or the desire to perform them were significantly associated with the perceived importance of the activities. The older population's age, education, attitudes, and personalities influence how they approach ICT. We propose a community-centered socio-ecological model to factor in these dispositional characteristics in future ICT training programs.